Light emitting diode (LED) therapy reduces local pathological changes induced by Bothrops asper snake venom - Campos, Gabriela Russo Soeiro (2018)
The therapeutic effect of the Light Emitting Diode (LED) treatment in two wavelengths (635 or 945 nm) was evaluated in the local pathological alterations induced by Bothrops asper snake venom. Mice received irradiation of infrared LED (120 mW, 945 nm) or red LED (110 mW, 635 nm) applied immediately, 1 and 2 h after venom injection. LED treatment reduced edema formation in the plantar region and gastrocnemius muscle and significantly reduced neutrophil migration and hyperalgesia after the venom injection. Also, both infrared LED and red LED treatment significantly reduced myonecrosis, as revealed by muscle CK and plasma CK levels. Histological analysis corroborated the reduction in the extent of venom-induced myonecrosis. In conclusion, our data demonstrates that PBM with LED light in both red and infrared wavelengths, when applied after envenomation in mice, reduces the extent of myotoxicity, edema, inflammatory infiltrate and hyperalgesia, suggesting that photobiomodulation is a potential therapeutic approach that should be further investigated for the treatment of local effects of Bothrops snakebite.